(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2005)
In the early Edo period the number of memorial cloisters (tacchu) increased, especially, at Daitoku-ji and Myôshin-ji temples. As a consequence, the hondô (kyakuden, hojo) were further developed in all aspects of architectural style, interior design and plan. This study will attempt to clarify the types of plans at memorial cloisters of both temples, by analyzing the arrangement and composition of the sanctuary, during the Edo period. In that period, the requirement of the rooms was interlaced with the function, and even dependent upon everyday life and the activities of religious services.